Gestión financiera de la empresa “Sara Papelería Popular” S.A. de la ciudad de Babahoyo. - Sisa Quingaguano, Carlos Joel (2022)
This case study was conducted with the objective of analyzing the economic situation through financial tools to determine the most influential factors in the profitability of the company “Sara Papeleria Popular” S.A. in the city of Babahoyo. This research aims to know the existence of an adequate internal control of the economic and financial information, analyze its accounts receivable, sales and inventories, analysis of the financial statements and the application of indicators that establish the veracity of the information. The methodology applied was the Quali-quantitative modality, using as research methods the analytical - synthetic and inductive - deductive that allowed the collection of economic information through the techniques of observation and interview, maintaining the types of bibliographic, descriptive and field research.